2015
DOI: 10.5604/12321966.1185761
|View full text |Cite
|
Sign up to set email alerts
|

First report of seroprevalence of <i>Toxoplasma gondii</i> infection in sheep in Pomerania, northern Poland

Abstract: Introduction and objective. Toxoplasmosis is parasitic disease which has economic relevance for both veterinary and human medicine. In sheep, toxoplasmosis is a major cause of abortion and can thus cause reproductive problems. The current study aimed to determine the occurrence of anti-Toxoplasma gondii IgG antibodies in sheep from 13 districts of northern Poland and thereby obtain actual data about T. gondii seroprevalence in this population of animals. Materials and methods. Blood samples from 1,646 animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The percentage of seropositive cattle noted in the present study (13.0%) is similar to the results of previous studies in selected regions of Poland (12.8-14.6%) [27,43,44] and much lower than those obtained almost 20 years ago in Lubelskie region (53.8%) [28]. A recent survey by Holec et al [45] concerning cattle from northern Poland showed a much lower seroprevalence (3.15%). In other European countries, the seroprevalence of T. gondii in cattle varies [22,36,[46][47][48][49] ranging from 7.5% in Portugal [38] to 83.3% in Spain [50].…”
Section: Discussionsupporting
confidence: 90%
“…The percentage of seropositive cattle noted in the present study (13.0%) is similar to the results of previous studies in selected regions of Poland (12.8-14.6%) [27,43,44] and much lower than those obtained almost 20 years ago in Lubelskie region (53.8%) [28]. A recent survey by Holec et al [45] concerning cattle from northern Poland showed a much lower seroprevalence (3.15%). In other European countries, the seroprevalence of T. gondii in cattle varies [22,36,[46][47][48][49] ranging from 7.5% in Portugal [38] to 83.3% in Spain [50].…”
Section: Discussionsupporting
confidence: 90%
“…A total of 176 serum samples of small ruminants (90 from sheep and 86 from goat) were received from the Veterinary Hygiene Station (Gdańsk, Poland). These sera were obtained from epidemiological studies conducted on a livestock population from the northern region of Poland [18]. All sera were classified on the levels of specific IgG antibodies according to the method described previously (an in-house ELISA assay [18]) and to the manufacturer's description of the diagnostic commercial kits: an agglutination test (Toxo-Screen DA, bioMérieux, Marcy-l'Étoile, France) and an immunofluorescence test using slides coated with T. gondii antigen (Toxo-Spot IF, bioMérieux, Marcy-l'Étoile, France).…”
Section: Serums Samples Of Small Ruminantsmentioning
confidence: 99%
“…These sera were obtained from epidemiological studies conducted on a livestock population from the northern region of Poland [18]. All sera were classified on the levels of specific IgG antibodies according to the method described previously (an in-house ELISA assay [18]) and to the manufacturer's description of the diagnostic commercial kits: an agglutination test (Toxo-Screen DA, bioMérieux, Marcy-l'Étoile, France) and an immunofluorescence test using slides coated with T. gondii antigen (Toxo-Spot IF, bioMérieux, Marcy-l'Étoile, France). Based on the results of the diagnostic tests, the sera were divided into seropositive and seronegative groups as follows: group I S -48 sera from naturally infected sheep (IgG positive), group I G -45 sera from naturally infected goat (IgG positive), group II S -42 sera from healthy sheep (IgG negative) and group II G -41 sera from healthy goat (IgG negative).…”
Section: Serums Samples Of Small Ruminantsmentioning
confidence: 99%
“…Furthermore, according to some authors, the prevalence in males was higher than females (Alvarado-Esquivela andal., 2013, Holec Gąsior and. However, according to the last, these results may differ because the male and female population consisted of a different number of animals, thus, the group of males represented only 5.6% of the tested population of animals (Holec Gąsior and al., 2015).…”
Section: Seroprevalence According To the Risk Factorsmentioning
confidence: 99%
“…Results from our study showed an increase in T. gondii seroprevalence with age confirming that a major source of infection for sheep is likely to be through the consumption of sporulated oocysts from the environment, and suggesting that most sheep acquired the infection post-natally (Dubey, 2009).These results are similar to those of some previous investigations (Wang and al., 20011, Van Der Puije and al., 2000, Rossi and al., 2011, Clementino and al., 2007, Holec Gąsior and al., 2015, Gebremedhin and al., 2014, Katser and al., 2011 indicating that age was an important factor for being seropositive as a measure of the cumulated life-time risk (Katser and al., 2001). In contrast, Rahman and al.…”
Section: Seroprevalence According To the Risk Factorsmentioning
confidence: 99%